Validation of the Jefferson Scale of Physician Empathy in Health Science Students at Universidad Andrés Bello, Concepción-Talcahuano - Mondaca Silva, Jorge Luis (Journal of Physiotherapy in Mental Health, 2025)
Abstract: Prior to the development of the Jefferson Scale of Physician Empathy (JSPE), no psychometric instrument had been specifically designed to assess empathy within the context of patient care. Although some tools existed to measure empathy in the general population, they lacked content specificity and contextual relevance for the healthcare framework. Despite being previously applied in Chile, the JSPE has not been validated for use among non-medical healthcare students, rendering the results obtained through such applications potentially unreliable. Objectives: To validate the Jefferson Scale of Physician Empathy (Health Professions Student version, HPS) among non-medical health science students at Universidad Andrés Bello. Materials and Methods: A cross-sectional study was conducted, using a stratified random sample of 212 students. Factorial analyses and statistical tests were applied, including the Kaiser-Meyer-Olkin (KMO) measure, Bartlett’s test of sphericity, ordinal alpha coefficient, and non-parametric tests (Wilcoxon-Mann-Whitney and Kruskal-Wallis). Results: The results demonstrated strong validity and internal consistency of the JSPE-HPS. Exploratory factor analysis identified three principal components. A general trend of declining empathy levels was observed as students progressed through their academic programs. No statistically significant differences in overall empathy scores were found between male and female students. Conclusions: The JSPE-HPS is a valid and reliable instrument for measuring empathy among non-medical health science students in Chile. Its validation constitutes a significant contribution, as it enables the targeted assessment of a core competency in the clinical-patient relationship, thereby supporting improvements in higher education training within the health sector.